Redesign of Standard Paddock Motorcycle Products Using the Quality Function Deployment (Q.F.D.) Method - Farid Alamsyah; Danang Sutoyo (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2023)
One of the two standard replacement aids for motorcycles is the Standard Paddock. The use of Paddock Standard itself was initially only used on sports or racing motorcycles because it did not have standards attached to the motorcycle. However, after the times and technology, leverage standards are in great demand by motorcycle lovers for daily activities and modifications. This research aims to design Paddock Standard tools that suit the wants and needs of consumers who are functional and able to provide safety, comfort, and convenience for their users. The design of the tool uses the Quality Function Deployment (Q.F.D.) method, which will later become a benchmark in making design concepts. There are two design concepts and one combined concept, where the selected is a combined concept A + B. After users test the concept and prototype of the design product as consumers, the average likes the product concept, which can provide more function than the previous tool. When asked if it can be implemented quickly and use the tool every day, most answer that they will probably use it more often every day.